Accepting Austerity or Grexit? Predicting Acceptance of Crisis Solution Strategies from People's image of the Greece-Eu Relationship, their own Position and Norms of Justice. Issue 1 (5th April 2017) - Prodromitis, Gerasimos; Chryssochoou, Xenia; Papastamou, Stamos
In recent years Greece has faced a terrible economic crisis that became social, political and humanitarian and challenged its relationship with the European Union. In this paper, through a survey research with an opportunity sample of Greek people (N = 739) of different ages and professions, we investigate whether participants' image of the relationship between Greece and the EU relates to their agreement with a) harsh austerity and decrease of national sovereignty, b) decrease of the public sector and c) Grexit measures. We hypothesized and observed that this relationship is mediated by beliefs about norms of justice and beliefs of individual mobility and relative position. In particular, a positive relationship between Greece and EU predicts agreement with harsh austerity and decrease of the public sector through justice beliefs of equity whereas the relationship with Grexit is not mediated by beliefs about norms of justice. In addition, perceiving the GR-EU relationship as a relationship of domination predicts the different measures through feelings of personal or relational relative position. Legitimation of a relationship of domination and acceptance of harsh measures is observed the less people feel relatively deprived personally in comparison to their past position or in comparison to others, whereas this relationship with Grexit is observed the more relative relational deprivation is felt. These results highlight that perception of asymmetric relationships and status (at an individual or group level) between the national group and the EU and distribution of resources should be taken into account when discussing measures to combat the crisis.